2008
DOI: 10.1186/1478-7547-6-16
|View full text |Cite
|
Sign up to set email alerts
|

People's willingness to pay for health insurance in rural Vietnam

Abstract: Background: The inequity caused by health financing in Vietnam, which mainly relies on out-ofpocket payments, has put pre-payment reform high on the political agenda. This paper reports on a study of the willingness to pay for health insurance among a rural population in northern Vietnam, exploring whether the Vietnamese are willing to pay enough to sufficiently finance a health insurance system.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
80
3
4

Year Published

2009
2009
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(100 citation statements)
references
References 27 publications
13
80
3
4
Order By: Relevance
“…The unadjusted mean amount to pay for VCHI per household was Int$114.38. This is far higher than the amount reported in other studies (Asenso-Okyere, Osei-Akoto, Anum, & Appiah, 1997; Binam, Nkama, & Nkendah, 2004;Dong, Kouyate, Cairns, Mugisha, & Sauerborn, 2003;Dror, Radermacher, & Koren, 2007;Lofgren et al, 2008;Onwujekwe et al, 2009) but comparable to the national average premium of VPHI, which is Int$109.36. Assuming that the probability of health care use is 0.5 and the annual expenditure per capita is Int$1360.37 (World Bank, 2012, this amount might be sufficient to cover the health care cost per 1000 individual population with a minimum of 25% paying participants.…”
Section: Discussioncontrasting
confidence: 38%
See 1 more Smart Citation
“…The unadjusted mean amount to pay for VCHI per household was Int$114.38. This is far higher than the amount reported in other studies (Asenso-Okyere, Osei-Akoto, Anum, & Appiah, 1997; Binam, Nkama, & Nkendah, 2004;Dong, Kouyate, Cairns, Mugisha, & Sauerborn, 2003;Dror, Radermacher, & Koren, 2007;Lofgren et al, 2008;Onwujekwe et al, 2009) but comparable to the national average premium of VPHI, which is Int$109.36. Assuming that the probability of health care use is 0.5 and the annual expenditure per capita is Int$1360.37 (World Bank, 2012, this amount might be sufficient to cover the health care cost per 1000 individual population with a minimum of 25% paying participants.…”
Section: Discussioncontrasting
confidence: 38%
“…This preference is higher than is found in Vietnam (20%) (Lofgren et al, 2008). Other studies did not compare the preferences between financing plans, and none were conducted in an upper-middle income country such as Malaysia.…”
Section: Discussionmentioning
confidence: 64%
“…Other studies have also shown that as the education level increases, the demand for health insurance increases [15,[18][19][20][21]. In our study, households whose heads have tertiary education were more likely to be covered under health insurance than those whose heads are in other education groups.…”
Section: Discussionsupporting
confidence: 58%
“…Moreover, providers are often reluctant to accept referred patients due to high and complicated transaction costs involved in being reimbursed [12]. These barriers to access may explain why willingness to pay for health insurance is found to be relatively low in a recent study in one rural district in Vietnam [13]. They may also explain partly why Vietnam's insurance schemes are found to have small or negligible impact on out-of-pocket health care spending [14].…”
Section: Introductionmentioning
confidence: 98%